Addressing Adoption in Counseling: A Study of Adult Adoptees' Counseling Satisfaction. Issue 3 (July 2017) - Baden, Amanda L.; Kitchen, Andrew; Mazza, Jonathan R.; Harrington, Elliotte Sue; White, Ebony E.
In this mixed-methods study, 118 adult adoptees completed an online survey gathering information on (a) reasons for seeking therapy, (b) preferences for therapists, (c) perception of therapists' degree of emphasis on adoption during therapy, and (d) relationship satisfaction with adoptive and birth family members. The participants also completed the Satisfaction With Therapy and Therapist Scale–Revised (STTS-R), Adoptive Identity Questionnaire (AIQ), and Rosenberg Self-Esteem Scale (SES). Findings were that the therapists' adoption competence was the most important factor for adoptees in selecting therapists, adoption-related issues were the most common reason adoptees sought therapy, and adoptees reported being more satisfied with therapy if their therapists placed emphasis on adoption regardless of the amount of attention that was focused on adoption.